The Effectiveness of YouTube Media-Based Learning on Students' Learning Motivation in SKI Learning at MTsN 7 North Aceh - Muharmi 'Asyrina; Azni Khairuni; Sarah Fazila (Universitas Islam Lamongan, 2026)
Although digital technology has significantly changed education, some teaching strategies are still ineffective, such as the Islamic Cultural History curriculum at MTsN 7 North Aceh. This study aims to examine how YouTube content affects students' motivation to learn in Islamic History (SKI) classes. The research methodology employed in this study is the quantitative technique of the one-group pre-experimental design. 21 students from class VII/D made up the research sample, and pretests, posttests, and observation results were used to gather data. The study's findings demonstrate that students' motivation to learn rose from 65.24 on the pretest to 78.67 on the posttest. The results of the paired t-test showed a difference between the scores prior to and following the use of YouTube media, with a value of 0.000 (<0.05). The pretest and posttest scores are well correlated, as indicated by the correlation value of 0.742. The conclusion shows that YouTube-based learning is effective in increasing students' learning motivation and creating an engaging and interactive learning atmosphere.